2022
DOI: 10.1007/s12210-021-01039-4
|View full text |Cite
|
Sign up to set email alerts
|

Polyclonal emergence of MDR Enterobacter cloacae complex isolates producing multiple extended spectrum beta-lactamases at Maputo Central Hospital, Mozambique

Abstract: Enterobacter spp. are important nosocomial pathogens responsible of a wide variety of infections, mainly due to Extended Spectrum β-Lactamase (ESBL) producing isolates, constituting a global public health issue in terms of clinical treatment and infection control, especially in low-income countries, where last-line treatment is often unavailable and there is weak nosocomial surveillance. In this study, we conducted a phenotypic and molecular characterization of 8 clinical Enterobacter spp. strains, isolated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Colistin (9.7%) and imipenem (14.2%) exhibited the lowest drug resistance rates among the isolates in this study. Other studies have reported lower antibiotic resistance rates in E. cloacae isolates against imipenem and colistin [20][21][22][23]. However, in Ebomah and Okoh survey, more than 70% of these bacterial strains were resistant to carbapenems [24].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Colistin (9.7%) and imipenem (14.2%) exhibited the lowest drug resistance rates among the isolates in this study. Other studies have reported lower antibiotic resistance rates in E. cloacae isolates against imipenem and colistin [20][21][22][23]. However, in Ebomah and Okoh survey, more than 70% of these bacterial strains were resistant to carbapenems [24].…”
Section: Discussionmentioning
confidence: 95%
“…Of 113 E. cloacae isolates, 89 (78%) exhibited multidrug resistance. Te frequency of MDR E. cloacae isolates has been reported to range from 69.9% to 75% in other studies [3,7,21]. In Uzunović et al's study, over 66% and 28% of E. cloacae isolates were resistant to cephalosporins and aminoglycosides, respectively [22].…”
Section: Discussionmentioning
confidence: 99%
“…ESBL-producing Klebsiella isolates are spreading worldwide [ 23 ], including in Africa [ 24 , 25 ]. In particular, in Mozambique, CTX-M-15 has been often reported in E. coli [ 26 , 27 , 28 ], in Klebsiella [ 14 , 16 ], and, recently, also in Enterobacter cloacae complex isolates [ 29 ]. In our studied isolates, the dissemination of the bla CTX-M-15 gene could be occurring through the mobility of plasmids, with IncF being the most common type, and the mobilization element IS Ecp1 or IS26 truncating IS Ecp1, which have been associated with the horizontal dissemination of resistance to beta-lactams [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…These infections can be especially dangerous and even fatal when they occur in immunocompromised individuals or patients such as neonates and those diagnosed with hematological diseases such as leukemia, diabetes mellitus, burns, or multiple traumas, especially those admitted to an intensive care unit (ICU) [ 6 , 7 , 11 , 12 ]. The World Health Organization (WHO) classifies the ECC carbapenemase enzyme producers, and/or extended spectrum β-lactamase (ESβL) as PRIORITY 1: CRITICAL [ 13 ], and some strains of this complex, belonging to sequence type (ST) ST171 and ST78, are considered high-risk disseminators clones of important resistance genes [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the resistance mechanisms to cephalosporins in Enterobacter spp. to that are first-to third generation include the production of chromosomal AmpC β-lactamases [ 9 , 11 ]; the expression of EsβLs [ 9 , 11 , 12 ], and the expression of SHV-12 β-lactamase, which contributes to the resistance or reduced susceptibility to the third and fourth generation [ 9 ]. The bla CTX-M-15 gene is the most common in different species of ECC found in clinical samples [ 11 , 12 ], which, when associated with other resistance mechanisms and to aminoglycosides, quinolones, carbapenems, and colistin, represent a serious health public problem due to the high mortality rate as a result of the difficulty involved in their treatment [ 12 ].…”
Section: Introductionmentioning
confidence: 99%